Εισαγωγή στην τεκτονική ανάλυση των ρηγμάτων της Ελλάδος - Παπανικολάου, Δ. ("Σεισμοί και κατασκευές", 1984)
The tectonic analysis of faults must include the geometric, kinematic, dynamic and temporal analyses. The results of the analysis must be coherent, with the σ2 axis parallel to the intersectionof a conjugate set of faults, whereas the slip lines must be perpendicular to it. Because of rejuvenation phenomena this relation is not always observed. Instead, the slip direction is observed to be oblique or subparallel to the intersection in the case of the activated faults during the earthquakes of 1981 in Kaparelli-Platees and in the case of the main fault set of Andros island in the Cyclades. Three areas are presented with inactive faults, active and inactive faults and active faults from NE Peloponnese. Finally, the generally active fault pattern of southern Greece is given and also a correlation of the fault pattern with the seismicity of the area, pointing out the existence of a relatively aseismic area with NHW-SSE trending faults in between two areas of high seismicity with B-W to ENE-KSW trending faults.
Keywords: active faults, Stress field, Parnon